Public Awareness of and Visitation to National Parks by Racial/Ethnic Minorities. Issue 8 (3rd August 2018) - Xiao, Xiao; Manning, Robert; Perry, Elizabeth; Valliere, William
ABSTRACT: National parks are an important manifestation of the United States' democratic ideal and attract more than 300 million visits annually. However, racial/ethnic minorities are substantially underrepresented among visitors, and this has led to three hypotheses—marginality, subculture, and discrimination—designed to help explain this pattern of visitation. Moreover, research suggests that the awareness of and visitation to national parks may relate to several variables, including race/ethnicity, socio-economic characteristics, and childhood visitation history. To investigate these issues, an online general population survey of New York City residents was conducted. Study findings suggest that (1) racial/ethnic minorities are underrepresented at some types of parks but not others, (2) Hispanics and Blacks generally have lower rates of awareness about national parks than Whites, and (3) awareness and childhood visitation history significantly affect visitation to national parks. These findings suggest potential approaches to enable and encourage diverse racial/ethnic groups to engage with national parks.